2015
DOI: 10.1186/s40591-015-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs in development and cancer: potential biomarkers and therapeutic targets

Abstract: Long noncoding RNAs are emerging as key players in various fundamental biological processes. We highlight the varied molecular mechanisms by which lncRNAs modulate gene expression in diverse cellular contexts and their role in early mammalian development in this review. Furthermore, it is being increasingly recognized that altered expression of lncRNAs is specifically associated with tumorigenesis, tumor progression and metastasis. We discuss various lncRNAs implicated in different cancer types with a focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
194
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(202 citation statements)
references
References 306 publications
(314 reference statements)
4
194
0
Order By: Relevance
“…LncRNAs are emerging as key players in different biological process, including cancer. In fact, lncRNAs have an advantage over protein-coding genes since their expression is more tissue specific, thus making them attractive as novel diagnostic tools [11]. Previously, we reported that human cells express a unique family of mitochondrial long ncmtRNAs (ncmtRNAs) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are emerging as key players in different biological process, including cancer. In fact, lncRNAs have an advantage over protein-coding genes since their expression is more tissue specific, thus making them attractive as novel diagnostic tools [11]. Previously, we reported that human cells express a unique family of mitochondrial long ncmtRNAs (ncmtRNAs) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biochemical diversity, a common theme for lncRNA function is temporal control of gene expression, regulating cellular programs that require highly specific and well timed responses to extracellular stimuli. [28][29][30] Unsurprisingly, misregulation of lncRNAs has been linked to the development of a multitude of human diseases including cancer 31 and heart failure. 32 The budding yeast Saccharomyces cerevisiae has been a robust system for genetic and molecular investigation of gene expression steps since its introduction as a model organism almost 30 y ago.…”
mentioning
confidence: 99%
“…We used a small interfering RNA (siRNA) that targeted UCA1 to normal cells, and their dysregulation could affect cell proliferation, apoptosis, autophagy, migration and metastasis. Our findings strongly suggest that lncRNAs could be used as a novel class of biomarkers as well as therapeutic targets for at least some types of cancers [22].…”
Section: The Effect Of Uca1 Inhibition On Cell Proliferation and Cellmentioning
confidence: 61%